2020
DOI: 10.1136/bmj.m3944
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19: risks to healthcare workers and their families

Abstract: Since the beginning of the coronavirus 2019 (covid-19) pandemic, healthcare workers have shown a remarkable resilience and professional dedication despite a fear of becoming infected and infecting others. 1 In a linked paper (doi:10.1136/bmj.m3582), Shah and colleagues now report robust and concerning findings regarding the risks of covid-19 among health workers and their households. 2 In a large register based cohort study, comprising the entire Scottish healthcare workforce, the authors compared the risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 16 publications
5
91
0
3
Order By: Relevance
“…The fear of contracting the virus revealed in this study was in agreement with previous studies [8,9]. The reasons for their fears were identified as family care in the event of self-isolation or quarantine, risk of infecting loved ones, lack of specific treatment and vaccine for COVID-19 [8,9], and lack of personal protective equipment (PPE) [10,11]. There are documented pieces of evidence that lack of protective equipment puts healthcare workers at risk of getting infected as well as their families [9,12].…”
Section: Discussionsupporting
confidence: 89%
“…The fear of contracting the virus revealed in this study was in agreement with previous studies [8,9]. The reasons for their fears were identified as family care in the event of self-isolation or quarantine, risk of infecting loved ones, lack of specific treatment and vaccine for COVID-19 [8,9], and lack of personal protective equipment (PPE) [10,11]. There are documented pieces of evidence that lack of protective equipment puts healthcare workers at risk of getting infected as well as their families [9,12].…”
Section: Discussionsupporting
confidence: 89%
“…Fear of being infected and infecting others has been commonplace during COVID-19 [ 30 , 31 ] and other pandemics (e.g., SARS [ 32 ]). These fears expressed during the first surge of COVID-19 in the UK were not unfounded [ 33 , 34 , 35 ] and subsequent research shows that during the first three months of the pandemic, healthcare workers in patient-facing roles were three times more likely to be admitted to hospital with COVID-19 than non-patient facing healthcare workers [ 36 ]. Risk was doubled for their household members [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Travel restrictions have caused challenges and uncertainties to foreign domestic workers, many of whom are women [29]. Informal care providers are often not directly protected by legal measures for health protection or adequate infectious disease control training [30]. In Muslim communities, evidence has shown that women are more likely to wear face coverings in public for religious reasons, but not in their houses while caring for others, while men wear masks for hygiene both inside and outdoors [31].…”
Section: Residual Risk Managementmentioning
confidence: 99%